Unexpected Finding of Delayed-Onset Seizures in HIV-Positive, Treatment-Experienced Subjects in the Phase Iib Evaluation of Fosdevirine (Gsk2248761). Issue 1 (January 2014) - Margolis, David A; Eron, Joseph J; DeJesus, Edwin; White, Scott; Wannamaker, Paul; Stancil, Britt; Johnson, Mark
Background: Fosdevirine (GSK2248761) is a non-nucleoside reverse transcriptase inhibitor with HIV-1 activity against common efavirenz-resistant strains. Two partially blind, randomized, Phase IIb studies were initiated (1 in treatment-naive and 1 in treatment-experienced subjects with HIV) to select a once-daily dose of fosdevirine for Phase III trials. Methods: In the SIGNET study, treatment-naive subjects were randomized 1:1:1 to receive once-daily fosdevirine 100 or 200 mg or efavirenz 600 mg, each along with tenofovir disoproxil fumarate/emtricitabine 300 mg/200 mg or abacavir/lamivudine 600 mg/300 mg. In the SONNET study, treatment-experienced subjects with non-nucleoside reverse transcriptase inhibitor-resistant HIV-1 were randomized 1:1:1 to treatment with fosdevirine 100 or 200 mg once daily or etravirine 200 mg twice daily, each along with twice-daily darunavir/ritonavir 600/100 mg and raltegravir 400 mg. The primary efficacy end point was the proportion of subjects with HIV-1 RNA<50 copies/ml. Safety and pharmacokinetics were also addressed. Results: A total of 35 subjects were exposed to fosdevirine 100 or 200 mg. Trials were halted when 5 treatment-experienced subjects (1 receiving fosdevirine 100 mg, 4 receiving fosdevirine 200 mg) developed new-onset seizures after ≥4 weeks of exposure to fosdevirine. There was no clear association between seizures and fosdevirine plasma drug levels. Time to seizure onset ranged from 28 to 81 days, and all 5 subjects experienced ≥1 seizure after drug discontinuation. Conclusions: The delayed onset of seizures after fos-devirine exposure and persistence after discontinuation is without precedent in antiretroviral drug development, leading to additional investigation and underscoring the need for careful subject monitoring.